Henry More and Thomas Hobbes’s Corporeal God - John Henry (Religions)
Thomas Hobbes’s strict monistic materialism led many contemporaries to believe he must be an atheist—to hold God to be a corporeal being, they claimed, was effectively to deny his existence. This paper is an addition to those works suggesting that Hobbes’s belief in a corporeal God must be taken seriously. Unlike earlier studies on this theme, it emphasises the change in Hobbes’s theism from an insistence early in his career that God’s nature is utterly unknowable (exempting God from the implications of Hobbes’s materialism) to a belief, first stated in 1668, that God is indeed a corporeal being. Seeking to explain this radical change, this article suggests that Hobbes’s later theology was influenced by the Cambridge Platonist Henry More, who developed the idea that God was an extended three-dimensional being. This article briefly considers alternative accounts, suggesting the influence of ancient Stoicism and aether theories, but affirms the influence of Henry More.